Ways of use of Economic-Mathematical Methods in Implementation of the State Program of Perfection of Continuous Educational System. - Gulamov Saidaxror; Erkin Ganiyev; X.M.Eshonqulov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article depicts the study of effective ways for utilizing Economic Mathematical Methods in Implementation of the State Program of Perfection of Continuous Educational System.